Long Peritoneal Dialysis Dwells With Icodextrin: Kinetics of Transperitoneal Fluid and Polyglucose Transport - Olszowska, Anna; Waniewski, Jacek; Stachowska-Pietka, Joanna; Garcia-Lopez, Elvia; Lindholm, Bengt; Wańkowicz, Zofia (Frontiers in Physiology, 2019)
Background and objective: During peritoneal dialysis (PD), the period of effective net peritoneal ultrafiltration during long dwells can be extended by using the colloidal osmotic agent icodextrin but there are few detailed studies on ultrafiltration with icodextrin solution exceeding 12 hours. We analysed kinetics of peritoneal ultrafiltration in relation to icodextrin and its metabolites for 16-hours dwells with icodextrin. Design, setting, participants, & measurements: In 20 clinically stable patients (mean age 54 years; 8 women; mean preceding time on PD 26 months), intraperitoneal dialysate volume (VD) was estimated from dilution of 125I-human serum albumin during 16-h dwell studies with icodextrin 7.5% solution. Osmolality and sodium were measured in dialysate and plasma. In 11 patients, fractional absorption of icodextrin from dialysate, dialysate and plasma amylase, and high and low (Mw <2 kDa) Mw icodextrin fractions were analysed. Results: Average VD increased linearly with no difference between transport types. At 16 hours the cumulative net ultrafiltration was 729337 mL (range -18 ml to 1360 mL) and negative in only one patient. Average transcapillary ultrafiltration rate was 1.40±0.36 mL/min, and peritoneal fluid absorption rate was 0.68±0.38 mL/min. During 16-hours, 41% of the initial mass of icodextrin was absorbed. Dialysate osmolality increased from 249.6±21.4 to 276.9±21.5 mOsmol/L (p<0.001) and plasma sodium decreased from 138.72.4 mmol/L to 136.53.0 mmol/L (p<0.05). Dialysate glucose G2–G7 oligomers increased due to increase of G2-G4 metabolites while G6-G7 metabolites and higher Mw icodextrin fractions decreased. In plasma maltose and maltotriose (G2-G3 metabolites) increased while higher Mw icodextrin oligomers were almost undetectable. Dialysate amylase increased while plasma amylase decreased. Conclusions: Icodextrin resulted in linear increase of VD with sustained net UF lasting 16 hours and with no significant difference between peritoneal transport types. In plasma, sodium and amylase declined, osmolality remained unchanged, G2-G3 increased whereas larger icodextrin fractions were not detectable. In dialysate, icodextrin mass declined due to decrease of hight Mw icodextrin fractions while low Mw metabolites, especially G2-G3, increased. The superiority of icodextrin as compared to glucose-based solutions may help to maintain fluid balance, which is especially important in anuric patients and in patients with fast peritoneal transport.